Fluktuasi parameter kualitas air di tambak super intensif udang vaname: Studi kasus pertambakan PT. Pillar Persada Parigi, Desa Bajo, Minahasa Selatan - Telaumbanua, Beatus H.; Pangemanan, Novie P.L.; Tumbol, Reiny A.; Undap, Suzanne L.; Tumembouw, Sipriana S.; Salindeho, Indra R.N. (e-Journal BUDIDAYA PERAIRAN, 2024)
The aim of this research was to determine the physical and chemical parameters of water quality in vanname shrimp culture in Pond PT. Pillar Persada Parigi, Bajo Village, South Minahasa. This research uses direct measurement methods in the field (In situ) and sample analysis in the laboratory. Water quality parameters measured in the field included temperature, degree of acidity (pH), salinity, dissolved oxygen, while ammonia, nitrite, nitrate, phosphate was analyzed at the Manado Industrial Research and Standardization Center. Water sampling and in-situ measurements were carried out in 4 ponds selected randomly from the ponds that were temporarily operating at the time of sampling. Based on the results of measurements of several physical and chemical parameters of water quality, both directly in the field (in situ) and the results of laboratory analysis of pond water samples from PT Pillar Persada Parigi, Bajo Village, South Minahasa Regency, a temperature range of 27 - 32˚C, salinity of 36 ppt was obtained. , dissolved oxygen 3.63 - 7.8 ppm, acidity degree (pH) 7.6 - 8.6, ammonia content 1 mg/L, nitrite <0.2757 mg/L, nitrate 5 mg/L, phosphate <0 .0027 – 1 mg/L. All parameters measured were still considered suitable for survival and supporting the growth of the vaname shrimp being cultured Keywords: vaname shrimp, dissolved oxygen, ammonia, nitrate